Determinan yang Berhubungan dengan Keterlambatan Keluarga Penderita Gangguan Mental Membawa Penderita Berobat ke Rumah Sakit - Santi Martini, Sujono Kardis,Tri Sejati (Berita Kedokteran Masyarakat (BKM), 2003)
Background: In Indonesia, especially in rural areas, many people have opinion that mental disorder are due to evil influence and other unreasonable etiology. Consequently, people with mental disorder are not eager to seek therapy from medical doctor or men-tal hospital, but they prefer to seek therapy from traditional healer, and shaman.Objective: To investigate determinants associated with the delay to bring a mental disorder patient to hospital.Method: This was an observational study with cross sectional design. The study was conducted at Dr. Radjiman Wediodiningrat hospital, Lawang, Malang for 5 months. The study subjects were members of family who have responsibility of the patient's life, understand with patient's history of the disease, and from low socio-economic. Sub-jects of this study consisted of 70 persons selected by using a consecutive sampling technique. Dependent variable of this study was the delay to bring a mental disorder patient to hospital, while independent variables of this study included perception on mental disorder patient and mental hospital, and handicap effect on patient and their family.Results: Most of the respondents had a good perception about mental disorder (67%). 46% had good perception and 54% had bad perception about mental hospital. Most of them (69%) felt that there was no handicap effect of mental disorder to patient and their family. The proportion of respondents who had been treated by Psychiatrist were about 43%, 28% by general doctor, 20% by kyai, 7% by dukun and 2% by paramedical pro-fessionals. Chi Square analysis showed that the previous effort for curing or seeking therapy was significantly related to delaying of family to bring a mental disorder patient to hospital (p = 0,002). However, relationship with the other variables were not signifi-cant including the perception of respondent about mental disorder (p = 0,909), and perception about mental hospital (p=0,775).Conclusion: Determinant related to the delay of family to bring a mental disorder pa-tient to hospital included the previous effort for curing or seeking therapy. Keywords: mental disorder, delaying, mental hospital